Outlook for Remittance Flows 2009-2011 : Remittances Expected to Fall by 7-10 Percent in 2009 - Ratha, Dilip; Mohapatra, Sanket; Silwal, Ani (World Bank, Washington, DC, 2012)
Newly available data show that remittance flows to developing countries reached $328 billion in 2008, larger than previous estimate of $305 billion. Remittances grew rapidly during 2007 and 2008, but have slowed down in many corridors since the last quarter of 2008. In line with a recent downward revision in the World Bank's forecast of global economic growth, also lowered forecasts for remittance flows to developing countries to -7.3 percent in 2009 from the earlier forecast of -5 percent. Flows to Latin America have been falling in a lagged response to the construction sector slowdown in the US, but there are emerging signs of a bottoming out. In contrast, flows to South Asia and East Asia have been strong; but there is risk of a slowdown going forward. The predicted decline in remittances is far smaller than that for private flows to developing countries. The resilience of remittances arises from the fact that while new migration flows have declined, the stock of migrants has been relatively unaffected by the crisis. Sources of risk to this outlook include uncertainty about the depth and duration of the current crisis, unpredictable movements in exchange rates, and the possibility that immigration controls may be tightened further in major destination countries.